Formulation and evaluation of controlled release matrix mucoadhesive tablets of domperidone using Salvia plebeian gum - Gurpreet Arora; Karan Malik; Inderbir Singh; Sandeep Arora; Vikas Rana (Wolters Kluwer Medknow Publications, 2011)
The aim of study was to prepare controlled release matrix mucoadhesive tablets of domperidone using Salvia plebeian gum as natural polymer. Tablets were formulated by direct compression technology employing the natural polymer in different concentrations (5, 10, 15 and 20% w/w). The prepared batches were evaluated for drug assay, diameter, thickness, hardness and tensile strength, swelling index, mucoadhesive strength (using texture analyzer) and subjected to in vitro drug release studies. Real-time stability studies were also conducted on prepared batches. In vitro drug release data were fitted in various release kinetic models for studying the mechanism of drug release. Tensile strength was found to increase from 0.808 ± 0.098 to 1.527 ± 0.10 mN/cm 2 and mucoadhesive strength increased from 13.673 ± 1.542 to 40.378 ± 2.345 N, with an increase in the polymer concentration from 5 to 20% (A1 to A4). Swelling index was reported to increase with both increase in the concentration of gum and the time duration. The in vitro drug release decreased from 97.76 to 83.4% (A1 to A4) with the increase in polymer concentration. The drug release from the matrix tablets was found to follow zero-order and Higuchi models, indicating the matrix-forming potential of natural polymer. The value of n was found to be between 0.5221 and 0.8992, indicating the involvement of more than one drug release mechanism from the formulation and possibly the combination of both diffusion and erosion. These research findings clearly indicate the potential of S. plebeian gum to be used as binder, release retardant and mucoadhesive natural material in tablet formulations.